Low-cost printed collinear array antenna. - Sierra-Perez, Manuel; Las Heras-Andres, Fernando; de Lope, Jose Antonio Gutierrez
This paper presents the design and antenna-prototype measurements of a low-cost antenna for DECT and LMDS system base stations (3400 to 3600 MHz). The specified pattern must be omnidirectional in the horizontal plane, having a maximum at the horizon. To produce this pattern, a linear array of printed patches, placed on both sides of a planar feeding structure, is designed The feeding structure is a symmetrical stripline, made with low-cost materials and designed to simplify the implementation tasks as much as possible.
Keywords: Microstrip arrays; Microstrip antennas; Stripline circuits; Omnidirectional pattern; Antenna radiation patterns; Cordless telephone systems; Land mobile radio equipment; Base station antennas